The effect of active recovery and cold water immersion on the subsequent knee extension and flexion strength - Strejcova, B.; Konopkova, R. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It is generally accepted that good recovery enables better performance and decreases the number of injuries in athletes. Athletes routinely employ post exercise strategies or practices in a bid to speed up recovery (Bleakley & Davison, 2010). Currently coldwater immersion recovery and active recovery have emerged as one of the most popular intervention enabling faster recovery. The aim of the study was to compare the effect of three kinds of recovery (active recovery, cold water immersion, passive recovery) on the medium- term knee strength in the extension and flexion. Methods: Fourteen athletes at the age of 26.6 ± 4.4 years performed, in a random cross-over design, 3 sessions with 3 repeated medium-term isokinetic tests. As active recovery we used walking for 10 minutes on the treadmill of 5.5 km/h speed and a gradient-was depended on the HR to achieve 60-65% of individual HRmax. As cold water therapy the participants were immersed up to their hips in the cold bath (13 ± 1°C) for 3x2, 5 min with 2 min out of the bath, repeated twice as intermittent protocol. The effect of active recovery, passive rest and cold water immersion were assessed by the 3x3 (time x recovery) repeated-measure ANOVA, respectively. Results: We found significantly lower absolute differences between first and third trial in knee extension for peak torque after the active recovery (> 0.9 Nm) than after the cold water immersion (<14.6 Nm) or the passive recovery (< 13.9 Nm). The decrease of the average power was significantly lower differences after the active recovery (< 5 W) than after the cold water immersion (< 23.7 W) or passive recovery (< 25.9 W). Maximal heart rate (HRmax) was significantly higher during the active recovery than during the cold water immersion and the passive recovery (173±14, 166±14 and 167±14 bpm). We have found significant differences in the average heart rates (HRavg) during active recovery, cold water immersion and passive recovery (124±8, 97±9 and 107±12 bpm) Discussion: The active recovery was the only method which showed lower decrease of knee strength in extension compared to passive recovery and cold water immersion. The fact that the current literature is not consistent in this topic is probably caused by the different localization of load and its subsequent effect on the blood circulation (Draper, Bird, Coleman, & Hodgson, 2006).